DIGITAL TRANSFORMATION IN INDONESIA: IS IT ELDERLY-FRIENDLY? - Mochamad Taufiqurrochman Abdul Aziz Zein; M. Khanif; Safiq Rosad; Ninik Agustin (PROCEEDING AL GHAZALI International Conference, 2023)
The acceleration of digital transformation in Indonesia has led to an increase in the country's Digital Competitiveness ranking, now at 45th in the world. However, it is important to further examine the community aspect of digital transformation in Indonesia, particularly in terms of digital readiness. The senior or elderly population is one group that is vulnerable in this regard. The objective of this study is to investigate the state of digital transformation in Indonesia, with a focus on the elderly population's digital readiness. The research employed the semi-systematic literature review method and the Publish or Perish application. The data collected was not computer-based or related to information systems for seniors or the elderly population. Instead, it was based on articles and papers collected from Scopus, Crossref, and Google Scholar journal databases. The research results indicate that digital transformation in Indonesia is a compelling topic. The Scopus, Google Scholar, and Crossref indexes contain 46, 185, and over 1000 articles on this theme, respectively. However, researchers in Indonesia have not studied the engagement and attention to seniors or the elderly population.